2017
DOI: 10.3390/insects8030084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxalic Acid on Apis mellifera (Hymenoptera: Apidae)

Abstract: Oxalic acid dihydrate is used to treat varroosis of Apis mellifera. This study investigates lethal and sublethal effects of oxalic acid dihydrate on individually treated honeybees kept in cages under laboratory conditions as well as the distribution in the colony. After oral application, bee mortality occurred at relatively low concentrations (No Observed Adverse Effect Level (NOAEL) 50 µg/bee; Lowest Observed Adverse Effect Level (LOAEL) 75 µg/bee) compared to the dermal treatment (NOAEL 212.5 µg/bee; LOAEL 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 18 publications
0
38
0
Order By: Relevance
“…Less likely, but not mutually exclusive, would be a reduction in size of the VÀ colonies (in contrast to larger V+ colonies) due to a postponed reaction to the oxalic acid treatment two months before the start of the experiment. Although a small batch of worker bees may have died directly after oxalic acid application and some of the remaining bees may have had a reduced lifespan (Rademacher et al 2017), bees are well able to cope with such accidental losses of workers (Johnson 2010, Perry et al 2015, colony sizes were similar at the start of the experiment, and moreover, no such pattern was found for NÀ vs. N+ colonies after its Fumagilin-B application (which could potentially also cause bee mortality).…”
Section: Relative Effects Of the Single Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Less likely, but not mutually exclusive, would be a reduction in size of the VÀ colonies (in contrast to larger V+ colonies) due to a postponed reaction to the oxalic acid treatment two months before the start of the experiment. Although a small batch of worker bees may have died directly after oxalic acid application and some of the remaining bees may have had a reduced lifespan (Rademacher et al 2017), bees are well able to cope with such accidental losses of workers (Johnson 2010, Perry et al 2015, colony sizes were similar at the start of the experiment, and moreover, no such pattern was found for NÀ vs. N+ colonies after its Fumagilin-B application (which could potentially also cause bee mortality).…”
Section: Relative Effects Of the Single Factorsmentioning
confidence: 99%
“…For the bees, this dermal application corresponds to circa 175 lg/bee, while the no-observed-adverse-effect level is 212.5 lg/bee (Rademacher et al 2017), The colonies that were treated had no capped brood during the application (Cornelissen et al 2013).The same colonies were additionally treated using Apistan (tau-fluvalinate 824 mg/strip; Vita Europe Ltd., Basingstoke, UK) to reduce mite levels in September. Varroa treatment consisted of an oxalic acid spray application (30 g/L oxalic acid dihydrate, 3%) prior to the start of experiment (May/June).…”
Section: Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Radenmacher and coworkers studied the effects of OA in bees. In their work, it was demonstrated that the lowest observed adverse effect level (LOAEL) after oral administration (72 h) was determined at 750 µg/g bee bw [5]. The same group reported that OA can provoke sublethal effects such as decreased longevity, although its mode of action is yet unknown.…”
Section: Introductionmentioning
confidence: 99%